The social world of the school : education and community in interwar London - Barron, Hester, 1980- (Manchester University Press, 2022)
"This book shows why the study of schooling matters to the history of twentieth-century Britain, integrating the history of education within the wider concerns of modern social history. Drawing on a rich array of archival and autobiographical sources, it captures in vivid detail the individual moments that made up the minutiae of classroom life. It focuses on elementary education in interwar London, arguing that schools were grounded in their local communities as lynchpins of social life and drivers of change. Exploring crucial questions around identity and belonging, poverty and aspiration, class and culture, behaviour and citizenship, it provides vital context for twenty-first century debates about education and society, showing how the same concerns were framed a century ago."--